Processing of Hybrid Perovskite Films Using Scalable Solution Methods for Application as Active Layers in Flexible Solar Cells (2025)
This thesis explores scalable solution-based processing techniques for fabricating hybrid perovskite films in flexible solar cells, with a focus on slot-die and doctor blade coating. With the global shift toward renewable energy sources, flexible perovskite solar cells (FPSCs) present a promising alternative to traditional photovoltaic devices. FPSCs are lightweight, compatible with various surfaces, and ideal for scalable production methods, such as roll-to-roll (R2R) processing, which aligns with the industry's demand for cost-efficient, large-area solar cells. However, large-scale fabrication of these solar cells introduces challenges, particularly in achieving high efficiency, uniformity, and stability under ambient processing conditions. This research explores the fundamental mechanics of meniscus formation in slot-die and doctor blade coating, highlighting the importance of a controlled coating window (CCW) for defect-free, high-quality film deposition. Ambient processing requires green solvent systems, with non-toxic alternatives such as γ-valerolactone and protic ionic liquids (PILs), which contribute to the formation of uniform films with superior structural integrity. These environmentally friendly solvents facilitate the perovskite's resilience to humidity, supporting stable fabrication outside controlled environments. The study assesses various compositions and solvent systems for their influence on film morphology, crystallinity, and perovskite performance in flexible solar cells. Additionally, it highlights the role of hole-transport and electron-transport materials in device architecture, explicitly evaluating the performance of nickel oxide (NiOx) as a hole-transport layer in flexible perovskite devices. Findings indicate that optimized NiOx layers significantly enhance the charge transport properties and stability of PSCs, particularly under thermal and mechanical stress. This work establishes optimized parameters for scalable solution processing and provides a comprehensive foundation for the industrial-scale production of flexible perovskite solar cells. The research advances local capabilities in solar technology, positioning this method as a viable addition to Colombia's renewable energy landscape while contributing valuable insights into the broader field of photovoltaic device engineering.